Nucleocapsid protein of SARS-CoV-2 phase separates into RNA-rich polymerase-containing condensates - Adriana Savastano (Nature Portfolio, 2020)
The SARS-CoV-2 viral genome is encapsulated by the nucleocapsid protein (NSARS-CoV-2) that is essential for viral replication. Here, the authors show that RNA induces liquid-liquid phase separation of NSARS-CoV-2 and how NSARS-CoV-2 phosphorylation modulates RNA-binding and phase separation and that these RNA/NSARS-CoV-2-droplets recruit and concentrate the SARS-CoV-2 RNA-dependent RNA polymerase complex in vitro, which would enable high initiation and elongation rates during viral transcription.